2015
DOI: 10.1111/caje.12166
|View full text |Cite
|
Sign up to set email alerts
|

Rogue aid? An empirical analysis of China's aid allocation

Abstract: Foreign aid from China is often characterized as “rogue aid” that is guided by selfish interests alone. We collect data on Chinese project aid, food aid, medical staff and total aid money to developing countries, covering the 1956–2006 period, to empirically test to what extent self‐interests shape China's aid allocation. While political considerations shape China's allocation of aid, China does not pay substantially more attention to politics compared to Western donors. What is more, China's aid allocation se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
149
5
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 225 publications
(175 citation statements)
references
References 43 publications
19
149
5
2
Order By: Relevance
“…Sanfilippo () also identifies market size and resource endowment as the main drivers of Chinese FDI, finding that these same factors attract Chinese aid projects in Africa even more. The above results contrast, however, with those of Dreher and Fuchs (), who provide empirical evidence showing that Chinese aid is independent of recipients' natural resources endowment and institutional characteristics. Thus, despite the common belief in the west, the empirical evidence on the resource‐seeking nature of China's involvement in Africa is actually mixed.…”
Section: China's Involvement In Africa: Nature and Causescontrasting
confidence: 84%
“…Sanfilippo () also identifies market size and resource endowment as the main drivers of Chinese FDI, finding that these same factors attract Chinese aid projects in Africa even more. The above results contrast, however, with those of Dreher and Fuchs (), who provide empirical evidence showing that Chinese aid is independent of recipients' natural resources endowment and institutional characteristics. Thus, despite the common belief in the west, the empirical evidence on the resource‐seeking nature of China's involvement in Africa is actually mixed.…”
Section: China's Involvement In Africa: Nature and Causescontrasting
confidence: 84%
“…The first group reflects selfish motives in aid allocation and is approximated by variables measuring donors' exports or bilateral trade with recipients or by variables describing different kinds of relationships and closeness between donors and recipients (common colonial links, geographic distance, cultural proximity, etc.). It is predicted that the volume of aid will be positively influenced by the intensity of donors' interests and by the proximity of mutual relationships [30][31][32][33][34][35].…”
Section: Methodsmentioning
confidence: 99%
“…To examine the claim that China's aid is characterized by -rogue aid‖ that guided by selfish interests alone, Dreher and Fuchs (2015) empirically tested to what extent self-interests shape China's aid allocation, based on the data on Chinese project aid, food aid, medical staff and total aid money to developing countries from 1956 to 2006. The evidence suggested that China's aid allocation does not depend on recipients' endowment with natural resources.…”
Section: China's Foreign Aidmentioning
confidence: 99%